Validity of Computer Based Learning Media to Improve Junior High School Students' Learning Outcomes on Ecosystem Topics - Harahap, Melanie Putri; Nasution, Nanda Eska Anugrah (META: Journal of Science and Technological Education, 2022)
The aim of this study was to determine the level of validity of computer-based learning media on ecosystem materials for grade VII junior high school students. The parameters measured were the validity of the computer-based learning media from the aspect of material, readability, interaction in media program, navigation button, grafity, readability, and interaction in media program. This study uses developmental stage that followed Dick and Carey (2001) model. The results of the validation by material and design experts were obtained using a questionnaire instrument. Based on the validation result of material expert showed that: (1) Material aspect was 89.28% (2) Readability aspect was 92.85% (3) Interaction in media program aspect was 95.83%. The validation result of media expert showed that: (1) navigation button aspect was 100% (2) Grafity aspect was 90.9% (3) Readability aspect was 96.4% and (4) interaction in media program aspect was 95.83%. It can be concluded that Computer based Learning Media product is feasible to use for learning in ecosystem material based on its validity.